A Brief History of the Dissemination and Reception of Karl Marx's Capital in the United States and Britain. (1st October 2016) - ,
Abstract : The year 2017, which marks the 150th anniversary of Karl Marx's Capital, presents an occasion to review the history of one of the most influential books ever written. This article gives an overview of the dissemination and reception of Capital in the United States and Britain over the last 150 years. This article, which is part of a larger ongoing project of writing a global history of the dissemination and reception of Capital (Musto and Amini 2017), seeks to illuminate the path forward in interpreting this important book by identifying how and why Marx's most piercing insights into the foundation of the capitalist mode of production have been received, understood, misunderstood, or ignored by his opponents and proponents.